Brain tissue partial pressure of oxygen predicts the outcome of severe traumatic brain injury under mild hypothermia treatment - Sun H; Zheng M; Wang Y; Diao Y; Zhao W; Wei Z (Neuropsychiatric Disease and Treatment, 2016)
Hongtao Sun,1,* Maohua Zheng,2,* Yanmin Wang,1 Yunfeng Diao,1 Wanyong Zhao,1 Zhengjun Wei1 1Sixth Department of Neurosurgery, Affiliated Hospital of Logistics University of People’s Armed Police Force, Tianjin, 2Department of Neurosurgery, The First Hospital of Lanzhou University, Lanzhou, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study was to investigate the clinical significance and changes of brain tissue partial pressure of oxygen (PbtO2) in the course of mild hypothermia treatment (MHT) for treating severe traumatic brain injury (sTBI). Methods: There were 68 cases with sTBI undergoing MHT. PbtO2, intracranial pressure (ICP), jugular venous oxygen saturation (SjvO2), and cerebral perfusion pressure (CPP) were continuously monitored, and clinical outcomes were evaluated using the Glasgow Outcome Scale score. Results: Of 68 patients with sTBI, PbtO2, SjvO2, and CPP were obviously increased, but decreased ICP level was observed throughout the MHT. PbtO2 and ICP were negatively linearly correlated, while there was a positive linear correlation between PbtO2 and SjvO2. Monitoring CPP and SjvO2 was performed under normal circumstances, and a large proportion of patients were detected with low PbtO2. Decreased PbtO2 was also found after MHT. Conclusion: Continuous PbtO2 monitoring could be introduced to evaluate the condition of regional cerebral oxygen metabolism, thereby guiding the clinical treatment and predicting the outcome. Keywords: severe traumatic brain injury, hypothermia, brain tissue partial pressure of oxygen, therapy